PERENCANAAN JALAN LINGKAR UTARA BREBES-TEGAL STA. 8+800 – STA. 17+377 - Abdullah Abdullah; Purnomo Purnomo; Y.I. Wicaksono; Bagus Hario Setiadji (Jurnal Karya Teknik Sipil, 2014)
The North Brebes-Tegal Ring Road is a primary arterial road corridor which are located in the North Coast of Java, Central Java across Brebes District (12.385 km) and Tegal (4.715 km), with a pavement structure used is a flexible pavement (asphalt). The road was built with the purpose to break traffic density that occurred in Brebes City and Tegal. In 2010, construction of The North Brebes-Tegal Ring Road began. However, in 2012 the construction activities temporarily halted due to several problems, one of them is the condition of the ground at a construction site in part marshes and ponds led to the implementation by using layers of flexible pavement (asphalt) is difficult to be implemented. This condition starts from STA. 8 +800 to STA. 17+377 from the direction of Brebes to Tegal. Therefore, in this final planning is The North Brebes-Tegal Ring Road, with alternative structures to replace the flexible pavement (asphalt) and rigid pavement structures, accompanied by stabilization of the soil to improve soil conditions by landfill swamp native land with material heaps of options so as to increase the value of the subgrade CBR for the better. Besides the implementation of soil stabilization is recommended to do a heap of soil reinforcement by utilizing sheet pile as a solution to overcome the problem of the construction of The North Brebes-Tegal Ring Road.